POLITIQUE MONETAIRE EN RDC : entre la crédibilité et l’optimalité. - MOBONDA, Ricky MOLOKO; Y’ANGANDUA, Jules Karl MBAY; SALAMA , Thabita NAFISA; NYADRI , Janvier EGUDRA; AMUNDE , Francis ANYOLE; AKOMBOYO, Senold TANDIA (IJRDO - Journal of Business Management, 2021)
The Central Congolese Bank have to choice between optimal monetary policy and credible monetary policy in order to avoid intertemporal incoherences (inflation and stabilization bias) generated by deviations. The lack of good trend of growth is an evidence that the leading of monetary policy is non efficient. This analysis with GMM thanks to the Barro and Gordon model prove that the conception and management of monetary policy is claimed in DRC.